2002
DOI: 10.1038/oby.2002.139
|View full text |Cite
|
Sign up to set email alerts
|

Binge Size Increases with Body Mass Index in Women with Binge‐Eating Disorder

Abstract: GUSS, JANET L., HARRY R. KISSILEFF, MICHAEL J. DEVLIN, ELLEN ZIMMERLI, AND B. TIMOTHY WALSH. Binge size increases with body mass index in women with binge-eating disorder. Obes Res. 2002;10: 1021-1029. Objective: To determine whether meal size is related to body mass index (BMI) in obese subjects with binge-eating disorder (BED). Research Methods and Procedures:Five groups of subjects each consumed two laboratory-test meals on nonconsecutive days. Forty-two women, categorized by BMI and BED diagnosis, were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
66
1
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(81 citation statements)
references
References 29 publications
12
66
1
2
Order By: Relevance
“…Alternately, our study may not have had enough power to detect these differences given the small sample size and the variability of the data. The finding, that there were no differences in the proportion of any of the macronutrients consumed by BED and non-BED obese in the laboratory, is consistent with the results reported by Goldfein et al 4 and Guss et al 7 The study by Yanovksi et al, 8 however, found that the BED group consumed a significantly higher proportion of energy from fat (38.9% vs. 33.5%) and lower proportion of energy from protein (11.4% vs. 15.4%) during the binge meal than the non-BED control group. Finally, one difference was found in the types of foods consumed by BED and obese control participants during the laboratory binge eating episodes.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Alternately, our study may not have had enough power to detect these differences given the small sample size and the variability of the data. The finding, that there were no differences in the proportion of any of the macronutrients consumed by BED and non-BED obese in the laboratory, is consistent with the results reported by Goldfein et al 4 and Guss et al 7 The study by Yanovksi et al, 8 however, found that the BED group consumed a significantly higher proportion of energy from fat (38.9% vs. 33.5%) and lower proportion of energy from protein (11.4% vs. 15.4%) during the binge meal than the non-BED control group. Finally, one difference was found in the types of foods consumed by BED and obese control participants during the laboratory binge eating episodes.…”
Section: Resultssupporting
confidence: 91%
“…The total energy intake for the BED group reported in this study (2178 kcal) falls within the range of previously reported measures of multiitem binge eating episodes, ranging from 1515 4 to 2963 kcal. 8 Guss et al 7 reported a positive correlation between food intake and BMI during binge eating episodes in BED, which may explain some of the variability in energy intake observed in the literature. The mean BMI of the BED group reported by Goldfein et al 4 was 33.4 kg/m 2 , while the mean BMI reported by Yanovksi et al 8 was 40.1 kg/m 2 .…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…[1][2][3][4][5] When the BE episodes occur at least 2 days a week over a 6-month period, associated with some characteristics of loss of control, and are not followed by compensatory behaviors oriented to losing weight, recent studies indicate the presence of a syndrome called binge eating disorder (BED). 2,3,[6][7][8][9][10] Nevertheless, it should be highlighted that this status does not have a defined diagnosis and is described in the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV-TR) as an unspecified eating disorder (ED); therefore, more studies are needed to clarify this situation. 11 The association between body image and BE is not entirely clear.…”
Section: Introductionmentioning
confidence: 99%